Quail Performance at the Starter-Grower Period Fed by Commercial Feed with the addition of Ginger and Turmeric - Ikhwan Fauzan; Deden Sudrajat; Elis Dihansih (Indonesian Journal of Agricultural Research, 2018)
Ginger and turmeric can be used as feed additive in the quail’s rations. An active substance in this Zingiberaceae family has good benefits for animals, especially quails. A research on the Quail Performance at the Starter-Grower Period fed commercial feed with the addition of ginger and turmeric had been conducted over the past five weeks. The purpose of this research was to know the effect of feed additive (ginger and turmeric flour) on the quail’s performance since the starter period up to the grower period. The data were 240 two day old quails. The experimental design used was a Complete Random Design (CRD) with 4 treatments and 4 replications, i.e. P0: feed controls without any addition, P1: addition of 1% ginger flour; P2: the addition of 1% turmeric flour; P3: the addition of 0.5% ginger flour plus 0.5% turmeric flour. The observed variables were the consumption of rations, body weights, FCR, mortality and depletion. The results showed that each of the treatment was not significantly different or had no effect on the performance of quails at the starter-grower period. It is necessary to do similar research by increasing the percentages administered to each of the treatments, so that the effect of administering the feed additive; i.e. ginger flour and turmeric flour can be obtained.